Puncak Teguh Cable Sdn. Bhd / Mohd Niqwan Uda Noor Abdul Karim... [et al.] - Uda Noor Abdul Karim, Mohd Niqwan; Yusof, Mohd Hairi; Jusoh, Muhamad Nasir; Marzuki, Mohd Shahril; Sulong, Sharizan Sabri (2005)
Puncak Teguh Cable Sdn. Bhd. will be launched at the early of the year 2006. The location that we choose is at Nibong Tebal because of it strategic location, where the market size is big and it is easy to go there We will running a telecommunication Contractor named as Puncak Teguh Cable Sdn. Bhd. From our research, this type of business has its own potential where now telecommunication industry in Malaysia is one of the most important things. Our target is to give every sector around us to choose our company for the job and services relating to our specialties. This will bring our team to develop a smart practice in every aspect especially business profits. Beside that, we also would like to take the opportunity to make our services be the best among the best. Finally, our main target is to expose our company to the outside region of Penang.